Pengaruh Penerapan Metode SQR3 (Survey, Question, Read, Recite, And Review) Berbantuan Cerita Bergambar Terhadap Kemampuan Membaca Permulaan Pada Peserta Didik Kelas I Gugus 1 Sudirman Surakarta Tahun Ajaran 2024/2025 - Sari, Ika Maharani Ayu Puspita; Wicaksono, Anggit Grahito; Jumanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of using the SQR3 (Survey, Question, Read, Recite, and Review) method combined with picture story media on the beginning reading skills grade I students in Gugus 1 Sudirman Surakarta in the 2024/2025 school year. The research approach used was quantitative with a pre-experimental design using a one group pretest-posttest pattern. The study population included all grade I students with a total of 162 students. The research sample consisted of 47 first grade students from Gandekan Public Elementary School in Surakarta and Purwodiningratan Public Elementary School in Surakarta. Based on the results of data analysis, the pretest average value of students' beginning reading ability was obtained at 64.04. After treatment using the SQR3 method picture stories, the posttest average value increased to 77.13. This shows an increase in beginning reading ability, where the posttest mean score was greater than the pretest mean score. Based on the paired sample t-test table, the significance value was 0.000, where the value is <0.05. so ho was rejected and ha was accepted. Furthermore, a tcount value of -16.102 was obtained, and this value was compared with the ttable at the degree of freedom (df) = N - 1, which is (47 - 1) = 46. Based on the ttable, the value of t0.05 = 2.459 was obtained. Then look for tcount = 16.10 and ttable = 2.459 then tcount ≥ ttable or 16.10 ≥ 2.459.